2016
DOI: 10.1002/micr.30043
|View full text |Cite
|
Sign up to set email alerts
|

Use of the retrograde limb of the internal mammary vein to avoid venous congestion in DIEP flap breast reconstruction: Further evidences of a reliable and time‐sparing procedure

Abstract: These findings suggest that when an additional venous outflow is required, the use of the IMV retrograde limb may help to avoid flap venous congestion. © 2016 Wiley Periodicals, Inc. Microsurgery 36:447-452, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 30 publications
3
55
0
1
Order By: Relevance
“…This hypothesis was not consistent with the results of our study, as no statistically significant evidence (P = 0.37) was found for this variable, being these communications more numerous in the case group than in the control group (48.86% vs. 23.81%). outflow from the superficial towards the deep system, several studies [6,7,11] have suggested that the absence of direct communications between the SIEV and the DIEV through venous perforators could favor congestion. However, statistically significant evidence was only reported by Schaverien et al [7] using magnetic angioresonance, and only when a DIEP flap was dissected based on just one perforator without direct SIEV-DIEV communication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis was not consistent with the results of our study, as no statistically significant evidence (P = 0.37) was found for this variable, being these communications more numerous in the case group than in the control group (48.86% vs. 23.81%). outflow from the superficial towards the deep system, several studies [6,7,11] have suggested that the absence of direct communications between the SIEV and the DIEV through venous perforators could favor congestion. However, statistically significant evidence was only reported by Schaverien et al [7] using magnetic angioresonance, and only when a DIEP flap was dissected based on just one perforator without direct SIEV-DIEV communication.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] However, the origin remains to be elucidated. Some triggering factors have been proposed: diameter of the SIEV larger than 1.5 mm, [6,13] absence of communications of both SIEVs crossing the abdominal midline, [6,13] absence of direct communications by perforators between the SIEV and the deep inferior epigastric vein (DIEV), [6] number of perforators of the flap, [5] and subcutaneous tissue thickness.…”
Section: Introductionmentioning
confidence: 99%
“…After thorough evaluation of all the articles retrieved on the subject of venous superdrainage, we have come down to 11 studies on various functional factors, [6][7][8][9][10][11][12][13][14][15][16] 18 studies reporting on the results of a single center on hydraulic constructs, 2,5,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] one review of the literature, 33 six studies on treatment algorithms, 1,15,[34][35][36][37] and one meta-analysis 38 (►Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The pooled meta-analysis of the four comparative studies showed that there was no statistically significant difference Padula, 2016 France 38 36 5 (13.2%) 1 (2.6%) 4 (10.5%) 0 (0%) 0 (0%) 0 (0%) Vijayasekaran, 2017 USA 30 30 2 (6.7%) 0 (0%) 3 (10.0%) 0 (0%) 0 (0%) 1 (3.3%) Figure 1 Forest plots demonstrating the odds ratio of ALT flap group versus jejunal flap group in terms of flap failure, fistula, stricture, and oral intake with random effects model meta-analysis. M-H, Mantel-Haenszel.…”
Section: One-vein Vs Two-vein Anastomoses Utilizing the Retrograde Lmentioning
confidence: 93%